Smoking as a triggering factor for alzheimer's disease: an integrative review (Research, Society and Development, 2020)
More than 50 million people worldwide suffer from dementia, with Alzheimer's being the most common, especially in smokers. The objective was to identify studies that related smoking to Alzheimer's. The methodology was an integrative literature review to respond to the PICO strategy (P: smokers; I: cigarette; C: non-cigarette users; O: cigarette as a triggering factor for Alzheimer's Disease): Smoking can be a triggering factor of Alzheimer's? The results showed smoking as a risk factor for the disease, in addition to chronic, recreational or passive smoking being associated with increased cerebral oxidative stress. Heavy consumption in middle age increased the risk of dementia by more than 100% compared to non-smokers. Thus, it is important to have measures and policies that guide about the risks and the reduction of cigarette consumption, contributing to greater development and quality of life for the population.